Diagnostic Value of Virtual Touch Tissue Quantification for Breast Lesions with Different Size. (2nd April 2014) - Yao, Minghua; Wu, Jian; Zou, Liling; Xu, Guang; Xie, Juan; Wu, Rong; Xu, Huixiong
Abstract : Purpose . To evaluate diagnostic value of the virtual touch tissue quantification (VTTQ) for breast lesions with different sizes. Materials and Methods . Patients with 206 breast lesions were categorized into three groups according to lesion size (<10 mm, 10–20 mm, and >20 mm). Breast lesions were examined by conventional ultrasound and VTTQ, and shear wave velocity (SWV) of each lesion and adjacent normal breast tissue were measured. Diagnoses were confirmed by pathological examination after surgery. The receiver-operating characteristic curve (ROC) analyses were performed to evaluate the diagnostic value of SWV, and the area under curves (AUC) was compared among groups. Results . SWV of malignant lesions was much higher than that of benign lesions, whereas the difference was not obvious for lesions <10 mm (P = 0.15 ). There was statistical significant difference of AUC between lesions <10 mm and 10–20 mm (P < 0 . 05 ), as well as lesions <10 mm and >20 mm (P < 0 . 05 ). The sensitivity of lesions <10 mm was 33.33%, which was relatively low compared to other groups. Conclusion . According to our results, VTTQ is a promising method for breast lesions >10 mm, and further studies were warranted to improve sensitivity of VTTQ for breast lesions <10 mm.